Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-03T20:44:09+01:00
3(x-3)= 3x -9
5(y+z)= 5y+ 5z
4(3x-y)= 12x- 4y
3(4a-c)= 12a - 3c
-2(7-4n)= -14 +6n
1/2(4z+2)= 2z +1
-1/3(6c-3)= -2c + 1
0,2(x-5y)= 0,2 x - y
3(1/3a+1)= a+ 3
2010-03-03T20:44:38+01:00
1. 3x- 3
2. 5y+ 5z
3. 12x- 4y
4. 12a- 3c
5. -14+ 8n
6. 2z+ 1
7. -2c+ 1
8. 0,2x- y
9. a+ 3
2010-03-03T20:45:04+01:00
1 3(x-3)=3x-9
2 5(y+z)=5y+5z
3 4(3x-y)=12x-4y
4 3(4a-c)=12a-3c
5 -2(7-4n)=-14+8n
6 ½(4z+2)=½*4z+½*2=2z+1
7 -⅓(6c-3)= -⅓*6-3*( -⅓)=-2c+1
8 0,2(x-5y)=0,2x-0,2*5y=0,2x-y
9 3(⅓a+1)=3*⅓a+3*1=a+3